Collaboration of the Office of Religious Affairs and Religious Figures in Improving Service Performance - Ardiansa B, Aco; Arif, Muhammad Ridwan; Wahyu, Wahyu (Journal La Bisecoman, 2024)
The collaboration between the Office of Religious Affairs (KUA) and religious leaders has been ongoing for a long time. The type of collaboration that occurs relates to religious services, such as marriage services, the organization of STQ/MTQ (the Quran memorization competition), and family development. These services serve as one of the performance indicators for the Office of Religious Affairs. This research aims to understand the collaboration between the Office of Religious Affairs and religious leaders in enhancing the performance of services at the Office of Religious Affairs, along with the supporting and inhibiting factors. The research was conducted in Mamuju Regency, specifically at the Office of Religious Affairs in the Mamuju and Tapalang Sub-districts. Data were obtained using observation, interviews, and documentation methods. The collected data were then analyzed using descriptive qualitative analysis through observations and interviews. The results of this study found that collaboration between the Office of Religious Affairs and religious leaders has been implemented for a long time. However, in this collaboration, there has not been a clear division of roles between the Office of Religious Affairs and religious leaders; collaborations are based on local customs. In this study, the researcher recommends utilizing an integrated service model, where all services provided by religious leaders related to KUA services can be internalized within the KUA services. "Integrated" can be interpreted as connected services with proper orchestration of actions that can be measured (evaluated).